Using Information Technology - Williams, Brian K.; Sawyer, Stacey C. (New York, 2015)
The tumultuos changes in the landscape of information technology over the last two years have led us to make extensive modififcations in this edition of Using Information Technology--to do not just a revision but a remaking and reimagining of this introductory computer concepts book.
Keywords: Computers; Information Technology; Telecommunication Systems